Celebrate golden anniversary Mangino couple celebrate 50th (Raton Range Raton, New Mexico, 1984)
Newspaper Article on the 50th Anniversary of Mike and Rose Mangino.
Master list item #: 11
File location is in the Raton File Cabinet
Keywords: Mangino, Mike; Mangino, Rose; Rose, Jeanne; Mangino, Pistol; Bray, Lonnie; Mangino, Spots; Magino, (Mrs); Williams, Sue; Williams, Louise; Dalio, Fred; Dalio, (Mrs); Pompeo, Albert; Pompeo, Patti; Pino, Adeline; Pino, Victor; Mangino, Mickey; Mangino, (Mrs); Mangino, Don; Mangino, (Mrs); Nauta, Lloyd D; Nauta, (Mrs); Annie Git Ur Guns; La Mesa Park; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Denver, Colorado; Pueblo, Colorado; Santa Fe, New Mexico; Trinidad, Colorado; Broomfield, Colorado